Update on Amyotrophic Lateral Sclerosis - Foyaca Sibat, Humberto; de Fatima Ibañez Valdés, Lourdes (IntechOpen, 2016)
This book contains selected peer-reviewed chapters which cover updated information on ALS written by international researchers. Update on Amyotrophic Lateral Sclerosis is comprised of 13 chapters from some of the world's top central nervous system researchers and neurologists to provide a timely review of the most recent developments in ALS, covering historic aspects, experimental animal models, genetics, pathogenesis, clinical aspects and imagenology among others. Contributors from Belgium, France, Japan, India, Italy, Mexico, Russia, South Africa, and Switzerland have collaborated enthusiastically and efficiently, dedicating their time to create this reader-friendly yet comprehensive work which includes many explanatory figures, tables and photos to enhance legibility and make the book clinically useful. We are looking forward with confidence and pride in the remarkable role that this book will play for a new vision and mission.